FUNCTIONAL CAPACITY, PHYSICAL ACTIVITY LEVEL AND NUTRITIONAL STATUS OF ELDERLY: A LITERATURE REVIEW (Fiep Bulletin - online, 2017)
Introduction: The aging of the world population is a theme emphasized in scientific research generally, this fact placesBrazil among the countries that will be affected significantly by the aging population, since, combined with this process, implies onthe rise of chronic diseases, loss of physical and mental abilities. Objective: To identify, through a literature review, the importance offunctional capacity, nutritional status and level of physical activity on the health of the elderly population. Methodology: The studyincluded original and review articles related to the topic, published in English, Portuguese and Spanish, from 1987, selected in thedatabases SciELO, Lilacs, PubMed and BIREME is using three sets of intersecting terms of bibliographic search, functionalcapacity, level of physical activity and nutritional status. Results: The described search strategy enabled locate 42 articles on thesubject studied, 11 of them reviews, 16 books, 2 dissertations / theses and 9 publications federal. Conclusion: Wear exposedhighlight it is important to employ health indicators able to identify elderly in the risk group of the above indicators in order to guideactions to maintain the functionality, keeping them in the community as long as possible with maximum independence and qualitylifetime.